Long Non-coding RNA MEG3 Activated by Vitamin D Suppresses Glycolysis in Colorectal Cancer via Promoting c-Myc Degradation - Zuo, Siyu; Wu, Lei; Wang, Yi; Yuan, Xiaoqin (Frontiers in Oncology, 2020)
Colorectal cancer (CRC), a common tumor, is characterized by a high mortality rate. Long non-coding RNA maternally expressed gene 3 (MEG3) serves a regulatory role in the carcinogenesis and progression of several types of cancer; however, its role in CRC remains largely unknown. The aim of this study was to explore the regulatory role and mechanism(s) of MEG3 in CRC. The Warburg effect or aerobic glycolysis is characteristic of the metabolism of tumor cells. To determine the effect of MEG3 on glycolysis of CRC cells, we used an XF analyzer to perform glycolysis stress test assays and found that overexpression of MEG3 significantly inhibited glycolysis, glycolytic capacity, as well as lactate production in CRC cells, whereas knockdown of MEG3 produced the opposite effect. Mechanistically, overexpression of MEG3 induced ubiquitin-dependent degradation of c-Myc and inhibited c-Myc target genes involved in the glycolysis pathway such as lactate dehydrogenase A, pyruvate kinase muscle 2, and hexokinase 2. Moreover, we found that MEG3 can be activated by vitamin D and vitamin D receptor (VDR). Clinical data demonstrated that MEG3 was positively associated with serum vitamin D concentrations in patients with CRC. We found that 1,25(OH)2D3 treatment increased MEG3 expression, and knockdown of VDR abolished the effect of MEG3 on glycolysis. These results indicate that vitamin D-activated MEG3 suppresses aerobic glycolysis in CRC cells via degradation of c-Myc. Thus, vitamin D may have therapeutic value in the treatment of CRC.